An ultra-wideband linear polarization conversion metasurface. (9th August 2018) - Dai, Huijuan; Zhao, Yongjiu; Sun, Hengyi; Chen, Jiaqing; Ge, Yue; Li, Zhuo
Abstract: An ultra-wideband reflective polarization conversion metasurface (PCM) is designed, which has a periodic multi-V-shaped subwavelength structure printed on a metallic plate backed with a dielectric substrate. Four resonances are generated under the normal incidence of plane waves, which leads to bandwidth expansion of the cross-polarization reflection. The proposed PCM can efficiently convert linear polarized waves to their orthogonal polarization counterpart in an ultra-wideband ranging from 14.3 to 43.2 GHz efficiently with an average polarization conversion ratio (PCR) of 96.7%.